Telaah Kritis Pemikiran Pendidikan Islam Al-Zarnuji dalam Kitab Ta‘lim Al-Muta‘allim - Ikhlas, Nur; Eva Dewi; Sutarmo (Program Studi Pendidikan Agama Islam IAIQI Al-Qur'an Al-Ittifaqiyah, 2025)
The contemporary challenges in Islamic education reveal a growing academic concern regarding the weak philosophical foundation that underpins the educational system, particularly in aspects of values, character, and spirituality. In this context, the thoughts of classical educational figures such as Al-Zarnuji become increasingly important to revisit. This study aims to critically examine Al-Zarnuji’s educational thought as outlined in his seminal work Ta'lim al-Muta'allim, focusing on educational goals, the roles of educators and students, learning methods, and curriculum, and linking them to the current needs of Islamic education. This research employs a qualitative library research method using descriptive-critical analysis of textual content. The findings indicate that education, according to Al-Zarnuji, aims to form a holistic personality integrating sincere intention, spiritual orientation, and social responsibility. Educators are viewed as moral-spiritual guides, while students are expected to embody humility, diligence, and discipline. The three main teaching methods promoted by Al-Zarnuji advice, dialogue, and discussion remain relevant in contemporary character education. Theoretically, this study enriches the discourse on classical Islamic educational thought that is relevant for reconstructing a value-based educational paradigm. Practically, the findings offer a foundation for educators, educational institutions, and policymakers to design learning systems that holistically integrate spirituality, ethics, and intellectual development.